MIS-C sequel to COVID-19 infection, diagnostic challenge and management. A case report - Paudeal, Subash; Das, Sunil Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Multisystem inflammatory syndrome in children (MIS-C) is a rare sequel to severe acute respiratory syndrome coronavirus (SARS-CoV-2). Clinical picture of MIS-C includes multi system inflammation alongside fever and severe illness with laboratory evidence of raised inflammatory markers. MIS-C may resemble toxic shock syndrome, complete or incomplete Kawasaki disease and macrophage activation syndrome. Actual management of MIS-C is yet to be formulated, currently treatment is supportive only. In addition, as MIS-C is a new clinical entity we do not know about its long-term prognosis.